2021
DOI: 10.1111/1462-2920.15636
|View full text |Cite
|
Sign up to set email alerts
|

Transcription activation of two clusters for exopolysaccharide biosynthesis by phosphorylated DctD in Vibrio vulnificus

Abstract: NtrC-mediated production of exopolysaccharides (EPS), essential components for Vibrio vulnificus biofilms, is highly increased in the presence of dicarboxylic or tricarboxylic acids. Gel-shift assays showed that regulation of the EPS-gene cluster I (EPS-I cluster) by NtrC was direct via binding of phosphorylated NtrC (p-NtrC) to the regulatory region of the EPS-I cluster. In contrast, p-NtrC did not bind to the EPS-II and EPS-III clusters, suggesting that NtrC regulation was not direct and another transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(36 citation statements)
references
References 41 publications
6
30
0
Order By: Relevance
“…Its sensor kinase, DctB, senses the ambient dicarboxylic acids and phosphorylates DctD, which in turn activates the transcription of genes encoding the uptake system(s) for dicarboxylic acids ( 15 ). In addition to nitrogen-fixing bacteria, many bacterial species, including the model foodborne pathogen Vibrio vulnificus , are also equipped with DctBD ( 16 ). In the genomes of V. vulnificus , two operons encoding the DctBD homologs, dctB 1 D 1 and dctB 2 D 2 , are present, but it was found that DctD 2 is responsible for activating the transcription of exopolysaccharide (EPS) EPS-II and EPS-III clusters in the presence of fumarate ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Its sensor kinase, DctB, senses the ambient dicarboxylic acids and phosphorylates DctD, which in turn activates the transcription of genes encoding the uptake system(s) for dicarboxylic acids ( 15 ). In addition to nitrogen-fixing bacteria, many bacterial species, including the model foodborne pathogen Vibrio vulnificus , are also equipped with DctBD ( 16 ). In the genomes of V. vulnificus , two operons encoding the DctBD homologs, dctB 1 D 1 and dctB 2 D 2 , are present, but it was found that DctD 2 is responsible for activating the transcription of exopolysaccharide (EPS) EPS-II and EPS-III clusters in the presence of fumarate ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to nitrogen-fixing bacteria, many bacterial species, including the model foodborne pathogen Vibrio vulnificus , are also equipped with DctBD ( 16 ). In the genomes of V. vulnificus , two operons encoding the DctBD homologs, dctB 1 D 1 and dctB 2 D 2 , are present, but it was found that DctD 2 is responsible for activating the transcription of exopolysaccharide (EPS) EPS-II and EPS-III clusters in the presence of fumarate ( 16 ). Notably, biosynthesis of EPSs, the loosely associated polysaccharides outside bacterial envelopes ( 17 ), is regulated at the transcription level via the involvement of DctD 2 , which activates the expression of EPS gene clusters in the presence of various kinds of dicarboxylic acids ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations